The influence of dietary fatty acid and fasting on the hepatic lipid metabolism of barramundi (Lates calcarifer). (27th October 2016) - Araújo, Bruno; Salini, Michael; Glencross, Brett; Wade, Nicholas
Abstract: For many fish species, dietary fish oil (FO) has been substituted with other oils such as poultry oil (PO) without affecting growth performance. However, in barramundi, the mechanisms by which fatty acid metabolism is regulated are poorly understood, and the effects of FO substitution are unknown. This study defined changes in the expression of genes controlling the metabolism of fatty acids in barramundi over a 24‐h time period after a single meal. From one to 12 h after a single feeding event, the expression of fatty acid synthesis genes in the liver was upregulated, while genes involved in the β‐oxidation showed minimal alteration. However, the expression of β‐oxidation genes was significantly correlated with the expression of genes regulating fatty acid synthesis. In a second experiment, the changes in liver fatty acid composition and gene expression were defined after FO was substituted with PO. Liver fatty acid profile reflected the diet composition, with some subtle exceptions supporting the enrichment of certain long‐chain polyunsaturated fatty acids in the liver. The fish from all experimental groups preferentially retained more docosahexaenoic acid than eicosapentaenoic acid in the liver, suggesting a bioconversion of this fatty acid to intermediate fatty acids. Replacement of FO with PO significantly regulated genes controlling both fatty acid synthesis and catabolism pathways, potentially related to a higher percentage of monounsaturated fatty acids, in the livers of fish fed these diets. The results demonstrated that diet composition significantly altered the lipid metabolism in barramundi and that there was a balance between direct dietary effects and endogenous synthetic capacity.